Pembelajaran Menyanyikan Lagu Daerah Cup Mak Ilang Menggunakan Media Gitar Pada Ekstrakurikuler di SMP Negeri 42 Palembang - Ridho Putra Widodo Raharjo; Silo Siswanto; Feri Firmansyah (Misterius: Publikasi Ilmu Seni dan Desain Komunikasi Visual, 2024)
Extracurricular music learning for school children, especially at junior high school level, aims to develop their creativity and talents. These activities include thorough planning, implementation and evaluation, not only to hone musical skills but also to stimulate their creative potential.